2016
DOI: 10.1021/acs.iecr.6b02323
|View full text |Cite
|
Sign up to set email alerts
|

Dealkylation of Aromatics in Subcritical and Supercritical Water: Involvement of Carbonium Mechanism

Abstract: Under hydrothermal environments covering the subcritical and supercritical regions of water, the involvement of the carbonium mechanism in the dealkylation of aromatics and its resulting influence on the pyrolysis of heavy oil were surveyed. α-Olefin groups, as either a part of straight chain hydrocarbons or the terminal of alkyl substitutes of aromatics, are protonated spontaneously by hydronium ions into carboniums, followed by βscission with similar reaction kinetic characteristics. The probability of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A common feature for the monomers obtained from lignin under neutral or reductive conditions is that they are substituted phenols bearing zero to two methoxyl groups in the ortho-position and an alkyl group in the para-position. If highly selective de-methoxyl [45][46][47][48][49][50][51][52][53] and de-alkyl [54][55][56][57][58][59][60][61] chemistry could simultaneously occur, one may anticipate that a mixture of substituted phenols to be converted into a single-compound phenol (Scheme 1). Notably, phenol is one of the most important aromatic chemicals utilized in industry reaching an annual production of 8.9 million tons [51], mainly used as synthetic polymer precursors such as bisphenol-A and nylon [62,63], as well as pharmaceuticals and herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…A common feature for the monomers obtained from lignin under neutral or reductive conditions is that they are substituted phenols bearing zero to two methoxyl groups in the ortho-position and an alkyl group in the para-position. If highly selective de-methoxyl [45][46][47][48][49][50][51][52][53] and de-alkyl [54][55][56][57][58][59][60][61] chemistry could simultaneously occur, one may anticipate that a mixture of substituted phenols to be converted into a single-compound phenol (Scheme 1). Notably, phenol is one of the most important aromatic chemicals utilized in industry reaching an annual production of 8.9 million tons [51], mainly used as synthetic polymer precursors such as bisphenol-A and nylon [62,63], as well as pharmaceuticals and herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Alibeyli et al [18] that non-aromatics hydrocarbons such as cyclohexane, hexane accelerated the hydrodealkylation reactions via the contribution of methyl and ethyl radicals formed with thermal or catalytic cracking of non-aromatics. It is reported that the hydrodealkylation mechanism of alkyl-benzene involves free radicals for thermal and carbonium ion mechanism in catalytic reactions [20,21], indicating that both mechanisms in the presence of n-decane over Cr-Al2O3 occur.…”
Section: Activity Results Of Catalysts the Effect Of N-decane On Mesimentioning
confidence: 99%
“…There are hydrated protons (H 3 O + ) in sub-CW, and their concentration strongly depends on the thermodynamic state of water. With a H 3 O + concentration up to 10 –5 M, the dealkylation of heteroatom-containing substituents in asphaltenes can be accomplished through the ionic mechanism, similar to the upgrading of biomass in sub-CW. Even though the substituents of asphaltenes consist of purely alkyl segments, dealkylation can still be achieved through free radical and ionic mechanisms . Being the heaviest oil component, asphaltenes with a coke-like supramolecular structure are dispersed in sub-CW .…”
Section: Results and Discussionmentioning
confidence: 99%
“…31−33 Even though the substituents of asphaltenes consist of purely alkyl segments, dealkylation can still be achieved through free radical and ionic mechanisms. 34 Being the heaviest oil component, asphaltenes with a coke-like supramolecular structure are dispersed in sub-CW. 35 In contrast, the substituents decomposed from asphaltenes have good solubility in sub-CW.…”
Section: Resultsmentioning
confidence: 99%